1997
DOI: 10.1099/0022-1317-78-1-147
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persistence of protective immunity in cynomolgus monkeys immunized with a recombinant vaccinia virus expressing the human T cell leukaemia virus type I envelope gene.

Abstract: To develop effective vaccines against infection with human T cell leukaemia virus type I (HTLV-I), we constructed a recombinant vaccinia virus (WR-SFB5env

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…31 For HTLV-1, it has been reported that vaccines expressing the envelope protein completely block infection in animal models. 33,34 Among HTLV-1 regulatory and accessory proteins, Tax is known to be the immunodominant protein, and a Tax vaccine was reported to protect against HTLV-1 infection in an animal model. 35 However, because of the high immunogenicity of Tax, its expression is frequently silenced or lost in ATL patients to evade the host immune surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…31 For HTLV-1, it has been reported that vaccines expressing the envelope protein completely block infection in animal models. 33,34 Among HTLV-1 regulatory and accessory proteins, Tax is known to be the immunodominant protein, and a Tax vaccine was reported to protect against HTLV-1 infection in an animal model. 35 However, because of the high immunogenicity of Tax, its expression is frequently silenced or lost in ATL patients to evade the host immune surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Monkeys and rabbits have been 4 used to examine HTLV-1 infection, replication, disease manifestations, immune response, and vaccine development [15][16][17][18][19][20]. However, rats and mice are more attractive models for HTLV-1 study because of the ease with which they can be genetically manipulated.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, successful passive immunization has been achieved with hyperimmune globulin from healthy donors (Murata et al, 1996;Akari et al, 1997). Successful immunization against HTLV-1 infection has also been accomplished with recombinant vaccinia virus expressing envelope or gag gene products in combination with DNA vaccines (Ibuki et al, 1997;Kazanji et al, 2001). …”
Section: Non-human Primate Modelsmentioning
confidence: 99%